Yield profile of tall fescue (Festuca arundinacea) in comparison with meadow fescue (F. pratensis) in Finland - Niemeläinen, Oiva; Jauhiainen, Lauri; Miettinen, Eero (Blackwell, 2001)
Yield profile characteristics of tall fescue (Festuca arundinacea Schreb.), cv. Retu, were studied and compared with those of meadow fescue (Festuca pratensis Huds.). The study was conducted in Finland and was based on official variety trial data recorded between 1980 and 1998 at 17 trial sites between latitudes 60o and 66o N. The crops were managed according to silage cutting regimes. The pattern of yield formation of the tall fescue cv. Retu differed significantly from that of meadow fescue cultivars, both in relation to growth rhythm within a growing season as well as in sward age. Tall fescue cv. Retu established slowly and the dry-matter (DM) yield from the first cut made in the first year of harvest was significantly smaller than that for meadow fescue. In the second and third years the DM yield from the first cut did not differ between tall fescue and meadow fescue. Tall fescue produced significantly higher DM yield as regrowth (second and third cuts) than meadow fescue. The sward age significantly affected total DM production. In first year swards there were no significant differences in total DM yield between tall fescue and meadow fescue, but in the second and third year swards tall fescue produced significantly higher DM yields than meadow fescue. The difference in yield profile between tall fescue and meadow fescue was similar in all the environments included in the study. DM yield for the first cut (kg DM ha-1) for tall fescue cv. Retu, in comparison with meadow fescue cultivars, was 2495 vs. 3099 (P <0.001), 3735 vs. 3741 (NS, P = 0.94), and 3553 vs. 3468 (NS, P = 0.30) in the first, second and third year swards respectively. The respective DM regrowth yields (second plus third cut) were: 6059 vs. 5416 (P <0.001), 5445 vs. 4221 (P <0.001), and 5580 vs. 4113 (P <0.001) in first second and third year swards. Total DM yields per season for tall fescue vs. meadow fescue were (kg DM ha-1) 8554 vs. 8515 (NS, P = 0.69), 9180 vs. 7962 (P <0.001), and 9133 vs. 7581 (P <0.001) in first, second and third year swards respectively. Over the three-year-sward rotation period, which is common in Finland, tall fescue produced on average 12% higher DM yield than meadow fescue. Both tall fescue and meadow fescue suffered little winter damage in Finnish conditions; the differences between cultivars of the two species were small. Results indicated that tall fescue cv. Retu is a productive and persistent forage species suited to Finnish growing conditions.
Keywords: Ka; nurmiviljely; nurmituotanto; nurmet; heinänurmet; säilörehunurmet; nurmikasvit; nurminata; ruokonata; talvenkestävyys; varieties; yield potential; winter damage; silage production; dry-matter yield